Perangcangan Sistem Informasi Film Berbasis WEB - Abdul Muni; Khairul Ihwan (JUTI UNISI, 2021)
WEB-Based Film Information System was created to facilitate the storage of film data. The purpose of this research is to develop an information system for storing films that are owned easily and efficiently in managing film types, genres and types. The development of an increasingly advanced modern market can be seen from the large number of films that continue to be released and the number of people watching films and choosing the desired film title. The purpose of this research is to produce a data processing that will be processed into information to improve the selection of films in the database. This system is made using the PHP programming language (Hypertext Preprocessor) and uses a MySQL database.